ADP-induced platelet aggregation and inhibition of adenylyl cyclase activity stimulated by prostaglandins : Signal transduction mechanisms - Puri, Rajinder N. (Biochemical pharmacology, 1999)
ADP is the oldest and one of the most important agonists of platelet activation. ADP induces platelet shape change, exposure of fibrinogen binding sites, aggregation, and influx and intracellular mobilization of Ca 2+. ADP-induced platelet aggregation is important for maintaining normal hemostasis, but aberrant platelet aggregation manifests itself pathophysiologically in myocardial ischemia, stroke, and atherosclerosis. Another important aspect of ADP-induced platelet activation is the ability of ADP to antagonize adenylyl cyclase activated by prostaglandins. ADP-induced inhibition of the stimulated adenylyl cyclase activity does not appear to play a role in ADP-induced platelet aggregation in vitro or in vivo. It is believed that a single ADP receptor mediates the above two ADP-induced platelet responses in platelets. The ADP receptor mediating ADP-induced platelet aggregation and inhibition of the stimulated adenylyl cyclase activity has not been purified. Therefore, the nature of molecular mechanisms underlying the two seemingly unrelated ADP-induced platelet responses remains either unclear or less well understood. The purpose of this commentary is to examine and make suggestions concerning the role of phospholipases and G-proteins in the molecular mechanisms of signal transduction underlying the two ADP-induced platelet responses. It is hoped that such discussion would stimulate thinking and invite future debates on this subject, and energize investigators in their efforts to advance our knowledge of the details of the molecular mechanisms of ADP-induced platelet activation.